Síndrome dos ovários policísticos: o impacto da informação na qualidade de vida, um ensaio clínico randomizado - Rosana Correia da Silva Azevdo (2016)
clinical expression. The clinical manifestations include menstrual irregularities, abnormal uterine bleeding, infertility, hirsutism, acne, alopecia, overweight and obesity, as well as increased risk of metabolic complications such as glucose intolerance, type 2 diabetes mellitus, hypertension and other cardiovascular diseases. All these conditions have negative effects on the quality of life of women with the syndrome.The objective of this study was to evaluate the impact of access to information on quality of life (QOL) of women with PCOS.The research consisted of a randomized clinical trial. Women with PCOS were recruited in the Hyperandrogenism Outpatient Clinic at Hospital das Clínicas UFMG. The participants were randomly divided into two groups matched for age, body mass index and education level: group 1 (n = 35) with access to information and group 2 (control, n = 45) in which theQOL was also evaluated, but that did not have access to information in the first stage of the study.The information provided to the patients of Group 1 was a leaflet prepared by the Hyperandrogenism Outpatient Clinic. The patients were encouraged to read the leaflet and also had a moment for your questions and concerns. The evaluation of quality of life in both groups, before and after the intervention, was carried out by applying two QOL questionnaires, the first, specific to the syndrome and the other generic, the Short Form- 36.The statistical analysis was carried out in SPSS software with significance level p < 0,05. Non-parametric tests were used. To study of categorical variables (qualitative) we used the Chi Square test and Fisher's exact test. For continuous variables (quantitative) we used the Mann-Whitney test. The final step was the analysis of the various domains of QOL questionnaires used in the study, comparing paired data from the first and the second assessments by using the Wilcoxon's test. The results showed that the QOL questionnaires did not detect differences between the intervention and the control groups before and after intervention. We discuss elements to contextualize the profile of participants and service conditions encountered, raising points for reflection. In conclusion, health information, although relevant and necessary, was not able, in this study, to modify the QOL of the evaluated participants.